Aplicação de sensores capacitivos para monitoramento da formação de parafina em oleodutos - Weber, Guilherme Heim (2013)
The crude oil extracted from oil fields is composed of various substances including different kinds of waxes. The conditions of flow and transport of this compound may cause wax to deposit and accumulate in the pipe wall, which may lead to gradually decrease the flow of crude oil. In this context, a measuring system was developed to monitor the deposition of wax on oil production lines. The developed system’s measuring principle is based on the fact that every substance has an electric permittivity value which may be used for monitoring. In this way, an electronic circuit was developed which is able to measure the variation of capacitance due to substances in contact with a coplanar capacitive sensor. In addition, software was developed to control the entire system and communicate with a microcontroller where the different tasks are executed. Different tests were performed to characterize and validate the measuring system. Among these, test of response time, linearity and measurements accuracy with known commercial capacitors, as well test with different substances in a broad range of electric permittivity values. Eventually, a test of wax solidification was performed, showing promising results for wax deposition monitoring.